A randomized crossover trial on the effect of plant-based compared with animal-based meat on trimethylamine-N-oxide and cardiovascular disease risk factors in generally healthy adults: Study With Appetizing Plantfood—Meat Eating Alternative Trial (SWAP-MEAT). Issue 5 (11th August 2020) - Crimarco, Anthony; Springfield, Sparkle; Petlura, Christina; Streaty, Taylor; Cunanan, Kristen; Lee, Justin; Fielding-Singh, Priya; Carter, Matthew M; Topf, Madeline A; Wastyk, Hannah C; Sonnenburg, Erica D; Sonnenburg, Justin L; et al.
ABSTRACT: Background: Despite the rising popularity of plant-based alternative meats, there is limited evidence of the health effects of these products. Objectives: We aimed to compare the effect of consuming plant-based alternative meat (Plant) as opposed to animal meat (Animal) on health factors. The primary outcome was fasting serum trimethylamine-N-oxide (TMAO). Secondary outcomes included fasting insulin-like growth factor 1, lipids, glucose, insulin, blood pressure, and weight. Methods: SWAP-MEAT (The Study With Appetizing Plantfood—Meat Eating Alternatives Trial) was a single-site, randomized crossover trial with no washout period. Participants received Plant and Animal products, dietary counseling, lab assessments, microbiome assessments (16S), and anthropometric measurements. Participants were instructed to consume ≥2 servings/d of Plant compared with Animal for 8 wk each, while keeping all other foods and beverages as similar as possible between the 2 phases. Results: The 36 participants who provided complete data for both crossover phases included 67% women, were 69% Caucasian, had a mean ± SD age 50 ± 14 y, and BMI 28 ± 5 kg/m 2 . Mean ± SD servings per day were not different by intervention sequence: 2.5 ± 0.6 compared with 2.6 ± 0.7 for Plant and Animal, respectively ( P  = 0.76). Mean ± SEM TMAO concentrations were significantly lower overall for Plant (2.7 ± 0.3) than for Animal (4.7 ± 0.9) ( P  = 0.012), but a significant order effect was observed ( P  = 0.023). TMAO concentrations were significantly lower for Plant among the n  = 18 who received Plant second (2.9 ± 0.4 compared with 6.4 ± 1.5, Plant compared with Animal, P  = 0.007), but not for the n  = 18 who received Plant first (2.5 ± 0.4 compared with 3.0 ± 0.6, Plant compared with Animal, P  = 0.23). Exploratory analyses of the microbiome failed to reveal possible responder compared with nonresponder factors. Mean ± SEM LDL-cholesterol concentrations (109.9 ± 4.5 compared with 120.7 ± 4.5 mg/dL, P  = 0.002) and weight (78.7 ± 3.0 compared with 79.6 ± 3.0 kg, P  < 0.001) were lower during the Plant phase. Conclusions: Among generally healthy adults, contrasting Plant with Animal intake, while keeping all other dietary components similar, the Plant products improved several cardiovascular disease risk factors, including TMAO; there were no adverse effects on risk factors from the Plant products. This trial was registered at clinicaltrials.gov as NCT03718988.